2013
DOI: 10.1371/journal.pone.0076746
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Identifies NF-κB as a Therapeutic Target in Renal Cancer

Abstract: ObjectiveTo determine the expression patterns of NF-κB regulators and target genes in clear cell renal cell carcinoma (ccRCC), their correlation with von Hippel Lindau (VHL) mutational status, and their association with survival outcomes.MethodsMeta-analyses were carried out on published ccRCC gene expression datasets by RankProd, a non-parametric statistical method. DEGs with a False Discovery Rate of < 0.05 by this method were considered significant, and intersected with a curated list of NF-κB regulators an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 55 publications
7
37
0
Order By: Relevance
“…Indeed, gene expression studies in large cohorts of RCC-bearing patients have suggested that some molecules such as IL-1, IL-6, TNF-α, C1q, and C1r could be implicated in the initiation and promotion of an intratumor inflammatory cascade (Peri, Devarajan, Yang, Knudson, & Balachandran, 2013;Romero et al, 2006;Tan et al, 2011). The RCC tumor cells probably orchestrate this inflammatory environment as suggested by the presence of several cytokines in the supernatant of RCC primary cultures, including IL-8, IL-10, TGF-β, GM-CSF, TNF-α, and VEGF (Gogusev, Augusti, Chrétien, & Droz, 1993;Knoefel et al, 1997;Lahn et al, 1999;Lee, Chun, Nadiminty, Lou, & Gao, 2007;Sievers et al, 2007).…”
Section: The Ccrcc Tumor Microenvironmentmentioning
confidence: 99%
“…Indeed, gene expression studies in large cohorts of RCC-bearing patients have suggested that some molecules such as IL-1, IL-6, TNF-α, C1q, and C1r could be implicated in the initiation and promotion of an intratumor inflammatory cascade (Peri, Devarajan, Yang, Knudson, & Balachandran, 2013;Romero et al, 2006;Tan et al, 2011). The RCC tumor cells probably orchestrate this inflammatory environment as suggested by the presence of several cytokines in the supernatant of RCC primary cultures, including IL-8, IL-10, TGF-β, GM-CSF, TNF-α, and VEGF (Gogusev, Augusti, Chrétien, & Droz, 1993;Knoefel et al, 1997;Lahn et al, 1999;Lee, Chun, Nadiminty, Lou, & Gao, 2007;Sievers et al, 2007).…”
Section: The Ccrcc Tumor Microenvironmentmentioning
confidence: 99%
“…Oncogenesis does not follow a strict pattern of signal relay, and is not confined to a single cell source, even if gene expression follows certain lineage-dependent restrictions. However, analysis of gene expression gives information on the NF-κB target gene signature that is essential to identify critical downstream pharmacological therapeutic targets [64]. When combined with the study of cultured cells, genetic analysis enables a personalized approach to tumors unforeseen by standard therapeutic protocols [65].…”
Section: Constitutive Nf-κb Activity and Feedback Changes Affect Cmentioning
confidence: 99%
“…With respect to RCC cancer overall survival, a recent meta-analysis on clear cell RCC gene expression identified a key NF-κB regulator (IKBKB) and established mediators of the NF-κB cell-survival and pro-inflammatory responses (MMP9, PSMB9, and SOD2), correlated with higher relative risk, poorer prognosis, and reduced overall patient survival (Peri et al 2013). In comparison, some have reported that NF-κB was not a prognostic factor in RCC survival (Kankaya et al 2015;Sourbier et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that p65 expression is upregulated and constitutively activated in RCC tissue (Djordjevic et al 2008;Peri et al 2013). NF-κB p65 and p50 have both been correlated with apoptotic and proliferation markers in RCC tissue (Kankaya et al 2015).…”
Section: (Morais Et Al 2011) Nf-κb Is Then Released Into the Nucleumentioning
confidence: 99%
See 1 more Smart Citation